Modulation of Respiratory Frequency by Peptidergic Input to Rhythmogenic Neurons in the PreBötzinger Complex - Gray, Paul A. (1999)
Neurokinin-1 receptor (NK1R) and μ-opioid receptor (μOR) agonists affected respiratory rhythm when injected directly into the preBötzinger Complex (preBötC), the hypothesized site for respiratory rhythmogenesis in mammals. These effects were mediated by actions on preBötC rhythmogenic neurons. The distribution of NK1R(+) neurons anatomically defined the preBötC. Type 1 neurons in the preBötC, which have rhythmogenic properties, expressed both NK1Rs and μORs, whereas type 2 neurons expressed only NK1Rs. These findings suggest that the preBötC is a definable anatomic structure with unique physiological function and that a subpopulation of neurons expressing both NK1Rs and μORs generate respiratory rhythm and modulate respiratory frequency.